Using Cognitive Event-Related Potentials in the Management of Alcohol Use Disorder: Towards an Individual Approach - Ingels, Anais; Fabry, Lauriane; Hanak, Catherine; Hanard, Florence; Kajosch, Hendrik; Kornreich, Charles; Campanella, Salvatore (Archives of Clinical and Medical Case Reports, 2022)
Objective: Alcohol use disorder (AUD) is associated with important cognitive impairments. These deficits play a significant role in the maintenance of consumption, despite the negative effect that it has on the daily life of alcohol addicts. The main objective of this case report is to illustrate how cognitive event-related potentials (ERPs) can be an adjuvant tool to propose an individualized and effective management of this disorder. Method: Three patients worried about their alcohol consumption were evaluated in a Go-NoGo task during an electroencephalographic recording. The peak amplitude of the NoGo N200, NoGo P300 and ERN evoked response were confronted to behavioral scores as well as to a clinical assessment. Results: ERPs allowed to distinguish between two types of cognitive deficits associated with alcohol consumption and treatment seeking. This was not possible when investigating only the behavioral and clinical scores which merely allowed to differentiate patients with AUD from the ones without AUD. Conclusion: Cognitive ERPs are biomarkers of great relevance in the management of AUD by identifying altered cognitive processes that are not observable at the single behavioral level. Significance: Further longitudinal studies should be designed in order to investigate the effect of an individualized cognitive retraining program, based on the observed cognitive alterations as well as on the relapse’ rate of these individual patients.